Borderline City Shifting borders in the wake of the COVID-19 pandemic in european cities and regions - Bentlin, Felix; Höfler, Jürgen; Million, Angela (Schriftenreihe Städtebau und Kommunikation von Planung, 2021)
Even before the spread of COVID 19 across the globe during the crisis of 2020, cities and regions acted as venues and drivers for a dualistic development dynamic by both creating and dissolving borders. The results obtained from various university seminars and a European summer school form the basis for a crisis manuscript, while serving to review the planning and design activities in different European cities and regions. For the first time ever, a network of students from the urban planning and design departments at 19 European universities have defined common requirements for crisis-resistant and people-friendly urban planning in Europe: On the one hand, crisis-related experiences act as catalysts for fundamental social, economic, and ecological changes, and, on the other hand, they accelerate changes that are already underway with regard to urban development policies. The crisis and border situations explored in this joint investigation extend beyond the mere operating principles of European cities and regions. In fact, as an endurance test and didactic example, they provide a guide for crisis-proof urban renewal in Europe. They lead the way in building a bridge between the European architecture and planning disciplines to create vibrant border landscapes.